Psychological determinants of re-socialization of convicts, as one of the important directions of recurrent crime prevention - Tsarkova, O.; Warina, H. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article is devoted to the analysis of the determinants of the successful establishment and functioning of the system of re-socialization of convicts. The relevance of this problem is determined by the contradiction between the need to return prisoners to a full life in society, the need to reproduce their family interaction skills, and the insufficient theoretical, methodological and methodical elaboration of this problem. The goal is to determine the features of resocialization and disclosure of the content and essence of adaptive family relations of convicts as a factor in the prevention of recidivism in modern scientific, theoretical and practical conditions of activity and functioning of the social and legal state. It has been determined that one of the most important aspects of the return of persons serving a sentence to a full-fledged life in society is the reproduction of their skills of adaptive social interaction, including adequate family behavior, correction of permanent and rigid role and behavioral stereotypes. The family relationship of the convicted person is considered as one of the reasons for his criminal behavior and the object of early prevention of unlawful behavior. Among the features of the family relations of convicts, the following characteristic is singled out: a significant weakening of their positive ties in society. The study led to the conclusion that the restoration of socially useful relations and the formation of adaptive family behavior, the legal status of the released without the provision of effective assistance is impossible. The resocialization of persons released from places of deprivation of liberty involves the active management of this process by penitentiary institutions and state bodies, the elimination or neutralization of negative factors that impede the return of persons who have served their sentences to socially useful activities. A comprehensive approach to the process of resocialization and to the study of this socio-legal category in modern conditions of humanization and democratization of society is needed.